2016
DOI: 10.1177/1756285615622736
|View full text |Cite
|
Sign up to set email alerts
|

A discrete-choice experiment to determine patient preferences for injectable multiple sclerosis treatments in Germany

Abstract: Objectives: The aim of this study was to assess the relative importance of features of a hypothetical injectable disease-modifying treatment for patients with multiple sclerosis using a discrete-choice experiment. Methods: German residents at least 18 years of age with a self-reported physician diagnosis of multiple sclerosis completed a 25-30 minute online discrete-choice experiment. Patients were asked to choose one of two hypothetical injectable treatments for multiple sclerosis, defined by different levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 33 publications
(90 reference statements)
2
30
0
2
Order By: Relevance
“…Seven studies (41.2%) used interviews at some point in the design stage, typically to refine an existing survey rather than as a basis for attribute development. Two out of these seven (28.6%) did not state how many interviews were carried out (Reed Johnson et al [29], Poulos et al [30]), and the average number for the remaining five is 10.3. Two studies (11.8%) (Wicks, et al [31] studies 1 and 2) did not state how attributes and levels were developed.…”
Section: Development Of Attributes and Levelsmentioning
confidence: 99%
“…Seven studies (41.2%) used interviews at some point in the design stage, typically to refine an existing survey rather than as a basis for attribute development. Two out of these seven (28.6%) did not state how many interviews were carried out (Reed Johnson et al [29], Poulos et al [30]), and the average number for the remaining five is 10.3. Two studies (11.8%) (Wicks, et al [31] studies 1 and 2) did not state how attributes and levels were developed.…”
Section: Development Of Attributes and Levelsmentioning
confidence: 99%
“…In all the GLP-1RA studies, a once-weekly dosing regimen was consistently preferred over a once-daily dosing regimen [30, 31, 36, 37, 46, 47]. Interestingly, DCE studies in patients with another chronic disease (multiple sclerosis; MS) also found that the frequency of injections was an important driver of preference for injectable MS treatments [48, 49]. …”
Section: Discussionmentioning
confidence: 99%
“…In a sample of 651 patients from the USA, the most important DMT factor was identified as a delay in years to disability progression, followed by the risk of progressive multifocal leukoencephalopathy 21. Poulos et al22,23 conducted two studies identifying the number of years until MS symptoms get worse as being the most important attribute, followed by flu-like symptoms, frequency of injections per month and number of relapses in the following years. In another study, 55 patients with RRMS completed a survey showing the highest preference for DMT that would improve MS symptoms and prevent progression, but not on relapse prevention 24.…”
Section: Discussionmentioning
confidence: 99%